Pre- and postnatal exposure to legacy environmental contaminants and sensation seeking in Inuit adolescents from Nunavik. - Avril Gagnon-Chauvin; Sandra W Jacobson; Joseph L Jacobson; Mathieu Fornasier-Bélanger; Yohann Courtemanche; Pierre Ayotte; Richard E Bélanger; Gina Muckle; Dave Saint-Amour (PLOS Global Public Health, 2023)
Despite extensive evidence from cohort studies linking exposure to lead (Pb), mercury (Hg) and polychlorinated biphenyls (PCBs) to numerous cognitive outcomes in children and adolescents, very few studies addressed reward sensitivity, a key dimension of emotional regulation. The present study aimed to examine associations between pre- and postnatal exposure to these environmental neurotoxicants and sensation seeking, a behavioral feature of reward. A total of 207 Inuit adolescents (mean age = 18.5, SD = 1.2) from Nunavik, Canada, completed the Brief Sensation Seeking Scale (BSSS-4) and Sensation Seeking- 2 (SS-2), two self-report questionnaires assessing proneness to sensation seeking. Prenatal, childhood and adolescent exposure to Pb, Hg and PCBs were measured in cord blood at birth and blood samples at 11 years of age and at time of testing. Multiple linear regression models were performed, potential confounders including participants' sociodemographic characteristics and nutrient fish intake were considered. Results showed that higher child blood levels of Pb (b = -0.18, p = 0.01) and PCB-153 (b = -0.16, p = 0.06) were associated with lower BSSS-4 total scores, while cord and adolescent blood PCB-153 levels were significantly related to lower SS2 total scores (b = -0.15, p = 0.04; b = -0.24, p = 0.004). Such associations persisted after further adjustment for co-exposure to concurrent contaminants. These associations were influenced by self-report positive affect and marginally moderated by sex. Sex differences were only observed for child PCB exposure, with the association for risk-taking sensation seeking observed only in girls but not in boys. Further research is warranted to assess the extent to which reduced sensation seeking in chronically exposed individuals affects their behaviors, well-being, and emotional regulation.